PENGARUH BRAND IMAGE, BRAND EXPERIENCE, DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPERCAYAAN KONSUMEN GUNA MENINGKATKAN KEPUTUSAN PEMBELIAN PRODUK SKINCARE SKINTIFIC (STUDI KASUS PADA KONSUMEN MAHASISWI DI KAMPUS 4 UNIVERSITAS MUHAMMADIYAH BENGKULU) - Eka Putri, Ninna Jalisma; Sismanto, Adi (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2024)
This study aims to analyze the direct and indirect influence  of Brand Image, Brand Experience  and Electronic Word of Mouth, on sales through trust. The data analysis technique uses path analysis. The population of this study is students of the management study program of the University of Muhammadiyah Bengkulu. Based on the results of research that has been conducted on the influence  of Brand Image, Brand Experience  and Electronic Word of Mouth, it has a direct effect on Trust. Brand Image, Brand Experience, and Electronic Word of Mouth have an indirect effect on Sales through trust. Key words: Brand Image, Brand Experience, Electronic Word of Mouth, Trust, sales.